PERANCANGAN ULANG ANTAR MUKA WEBSITE SEBAGAI MEDIA INFORMASI PERGURUAN TINGGI UNIVERSITAS TELKOM - MOCHAMMAD FAIZAL; ANDREAS RIO ADRIYANTO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Today, technology develops rapidly, where people can not be separated from the internet. In the internet, known a media named website, and ideally the Telkom University should implement the use of website to support various activities that take place in it, because it supports the vision of the Telkom University to be a